2012
DOI: 10.4103/2152-7806.96154
|View full text |Cite
|
Sign up to set email alerts
|

Primary spinal extradural Ewing′s sarcoma (primitive neuroectodermal tumor): Report of a case and meta-analysis of the reported cases in the literature

Abstract: Background:Primary spinal primitive neuroectodermal tumors (PNET) and/or spinal extraskeletal Ewing's sarcoma family tumors (ESET) are rare lesions appearing in the spinal extradural space. One hundred forty-one primary spinal PNETs, including 29 intramedullary lesions, have been reported in the literature. Encountering a case of primary epidural EES/peripheral PNET (pPNET) in sacral level, which is the fifth one occurring at this level in the literature, we have tried to conduct a meta-analysis of the reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 68 publications
(80 reference statements)
2
39
0
Order By: Relevance
“…The review of the literature on combined pediatric and adult spinal EES/pPNET showed that the lumbar region is the most common site, followed by the thoracic and cervical spine, with the sacral region being the least common (5% of cases) [7, 12]. However, in our analysis of the 46 adult epidural EES/pPNET cases (including our case), we found that the most common site was the thoracic spine (17 cases), followed by lumbar (13 cases), cervical (13 cases), and sacral segments (3 cases).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The review of the literature on combined pediatric and adult spinal EES/pPNET showed that the lumbar region is the most common site, followed by the thoracic and cervical spine, with the sacral region being the least common (5% of cases) [7, 12]. However, in our analysis of the 46 adult epidural EES/pPNET cases (including our case), we found that the most common site was the thoracic spine (17 cases), followed by lumbar (13 cases), cervical (13 cases), and sacral segments (3 cases).…”
Section: Discussionmentioning
confidence: 99%
“…The mean diagnostic delay calculated from the previous cases is 4.5 months [7], which is explained by nonspecific symptoms at disease onset. The symptoms commonly include back and/or radicular pain in all patients, paresis in about 70%, sensory disturbances in 35%, and to lesser extent bladder and bowel dysfunction in about 12% of patients [7, 15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations